Original paperSensitization to cereal allergens in children with atopic dermatitis - Cudowska, Beata; Marcinkiewicz, Sylwia; Kaczmarski, Maciej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction: Allergy to grain proteins affects approximately 14-18% of patients with atopic dermatitis and usually manifests in late reactions and symptoms of the skin and gastrointestinal tract. Aim: To evaluate the prevalence of allergy to cereals in children with atopic dermatitis, its impact on the course of the disease and the coexistence of sensitization to food and other airborne allergens. Material and methods: The study included 61 children with atopic dermatitis. Diagnosis of sensitization to cereal allergens was carried out on the basis of skin prick tests, determination of specific IgE, and atopy patch tests. Results: Twenty-six children (43%) had sensitization to cereal allergens. The other 35 patients were enrolled in the control group. In the study group, immediate-type reactions were confirmed in 46% of patients, late-type in 65%. The most common was allergy to proteins of wheat and rye. There were no significant differences between the SCORAD, peripheral blood eosinophilia and total IgE in the study and control group. There was also more frequent sensitization to other inhalant and food allergens, allergic rhinitis and asthma in the investigated group of children. Conclusions: 1. Sensitization to cereal allergens is a common phenomenon in children with atopic dermatitis and should be taken into account in the diagnostic process. 2. There was no relationship between the occurrence of sensitization to these allergens and the severity of skin lesions assessed by the SCORAD scale. 3. For children who are allergic to cereal proteins, there is not predisposition to hypersensitivity to pollen allergens and rhinitis or bronchial asthma. 4. In the case of positive results of allergy to cereal proteins and severe exacerbations of atopic dermatitis there should be considered some attempts of elimination and provocation tests.